2009
DOI: 10.1021/la901808t
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Growth of Vapor-Deposited n-Dotriacontane Films Studied by X-ray Reflectivity

Abstract: We have used synchrotron X-ray reflectivity measurements to investigate the structure of n-dotriacontane (n-C(32)H(66) or C32) films deposited from the vapor phase onto a SiO(2)-coated Si(100) surface. Our primary motivation was to determine whether the structure and growth mode of these films differ from those deposited from solution on the same substrate. The vapor-deposited films had a thickness of approximately 50 A thick as monitored in situ by high-resolution ellipsometry and were stable in air. Similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 15 publications
4
13
0
Order By: Relevance
“…We have investigated three possible explanations for this step up in the ellipsometric signal dP. Based on recent synchrotron x-ray reflectivity measurements on similar films, 12 we proposed that this step is due to a "chainmelting" transition in which gauche defects are introduced collectively into the molecules. This transition produces a slight increase in the density within the monolayer islands, which is observed as a step up in the ellipsometric signal.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have investigated three possible explanations for this step up in the ellipsometric signal dP. Based on recent synchrotron x-ray reflectivity measurements on similar films, 12 we proposed that this step is due to a "chainmelting" transition in which gauche defects are introduced collectively into the molecules. This transition produces a slight increase in the density within the monolayer islands, which is observed as a step up in the ellipsometric signal.…”
Section: Discussionmentioning
confidence: 99%
“…This value is very close to the shrinking of 40.3 Å observed with XRR. 12 Considering the almost constant step height we measured at monolayer coverages of ϳ50% and ϳ70%, a linear scaling may be regarded as the upper limit for a dP correction.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior to F68 deposition, we cleaned the silicon substrate by immersing it into a solution of sulfuric acid and hydrogen peroxide (70% H 2 SO 4 1 30% H 2 O 2 ) at 90 C for 30 min, providing an hydrophilic substrate surface. 18 Previous analysis of X-ray reflectivity curves, 17 indicated that the thickness of the SiO 2 coating was 12 Å . This cleaning procedure does not remove the native oxide layer and provides very reproducible substrates.…”
Section: Morphological Analysis By Atomic Force Microscopymentioning
confidence: 99%